UPAYA KEMENTERIAN AGAMA DALAM MENANGKAL RADIKALISME DI KABUPATEN GRESIK - Mohammad Maulana Iqbal; Agus Machfud Fauzi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
Radicalism is not a new face for the Gresik people. However, since its existence, radicalism has continued to exist as an element which has disturbed the stability of the social order in society. Therefore, it is necessary to have certain parties such as the Ministry of Religion of Gresik Regency who are able to ward off radicalism for the sake of equilibrium in the social order in society. This study aims to see the various efforts made by the Ministry of Religion of Gresik Regency in counteracting radicalism in Gresik Regency. Through the perspective of Social Action theory initiated by Max Weber, it will show the ratio pattern used by the Ministry of Religion of Gresik Regency in acting to counter radicalism. More than that, this research also uses qualitative methods by conducting direct interviews with the Ministry of Religion of Gresik Regency. Through interviews, it was found that efforts to counter radicalism by the Ministry of Religion of Gresik Regency were carried out by means of cooperation with certain parties. More than that, the Ministry of Religion of Gresik Regency also prioritizes a dialogical approach to groups indicated as radical in order to instill a more moderate mindset in these groups. Based on some of these efforts, it shows that the Ministry of Religion of Gresik Regency uses the Weber Instrumental Rationality pattern in its cooperation on several parties and also the use of Weber's Value Rationality in the orientation that it wants to achieve in an action